Nilai Kearifan Lokal sebagai Pilar Pemertahanan Teater Tradisional Mendu Kalimantan Barat - Gunta Wirawan; Eti Sunarsih; Wahyuni Oktavia; Safrihady Safrihady; Zulfahita Zulfahita; Sri Mulyani; Lili Yanti (Balai Bahasa Sulawesi Selatan, 2024)
Traditional theater Mendu has become the identity of the West Kalimantan Malay community because in the Mendu performance various Malay elements are preserved such as customs, oral traditions, oral literature, regional languages, traditional clothing, regional dances, Malay pencak silat and other values. These values are local wisdom that can be a pillar in maintaining traditional theater Mendu. This research aims to describe the local wisdom values contained in the traditional theater Mendu of West Kalimantan. The method used is a qualitative descriptive method with an ethnographic approach. The research results show that Mendu has good local wisdom values, that are worth preserving. These values are integrated into a Mendu performance, including: (1) the value of Malay identity, (2) religious values, (3) the value of the tradition of cooperation, (4) the value of preserving regional languages, (5) the value of preserving oral literature, (6) the value of preserving traditional pencak silat, (7) the value of preserving traditional Malay clothing, (8) the value of preserving regional dances, (9) the value of Malay customs, (10) the value of community education, (11) the value of kinship and social solidarity. AbstrakTeater tradisional Mendu menjadi identitas masyarakat Melayu Kalimantan Barat dikarenakan dalam pertunjukan Mendu tersimpan berbagai unsur kemelayuan seperti adat istiadat, tradisi lisan, sastra lisan, bahasa daerah, pakaian adat, tari daerah, pencak silat Melayu, dan nilai-nilai lainnya. Nilai-nilai tersebut merupakan kearifan lokal yang dapat menjadi pilar dalam pemertahanan teater tradisional Mendu. Tujuan penelitian ini adalah mendeskripsikan nilai-nilai kearifan lokal yang terdapat dalam teater tradisional Mendu Kalimantan Barat. Metode yang digunakan adalah deskriptif kualitatf dengan pendekatan etnografi. Hasil penelitian menunjukkan bahwa Mendu memiliki nilai kearifan lokal yang baik, sehingga patut untuk dilestarikan. Nilai-nilai tersebut terintegrasi dalam sebuah pertunjukan Mendu, antara lain: (1) nilai identitas melayu, (2) nilai religi, (3) nilai tradisi gotong royong, (4) nilai pemertahanan bahasa daerah, (5) nilai pelestarian sastra lisan, (6) nilai pelestarian pencak silat tradisional, (7) nilai pelestarian pakaian adat melayu, (8) nilai pelestarian tari daerah, (9) nilai adat istiadat Melayu, (10) nilai edukasi masyarakat, (11) nilai kekeluargaan dan kesetiakawanan sosial.